Activity Analysis of the Utilization of E-Learning in Student Learning at State Vocational High School 2 Nabire Using the Technology Acceptance Model - Sartje Mala Rangkoly; Wing Wahyu Winarno; Asro Nasri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research aims to find out activity analysis of the utilization of e-learning in student learning at State Vocational High School 2 Nabire using the technology acceptance model. Respondents were carried out at State Vocational High School 2 Nabire with the number of students being 632 using a sample calculator, so the responses obtained were 84 students consisting of majors namely Construction and Property Engineering, Electrical Power Installation Engineering, Audio Video Engineering, Motorcycles, Computer Engineering and Network with Class X, XI, and XII. Through this research, it is hoped that it can provide an evaluation of an event and teaching and learning process within the scope of State Vocational High School 2 Nabire. With the number of students is 632 students with the sample taken is 84 students. The research analysis uses a structural equation model, using WarpPLS. The results showed that usability has a positive and significant effect on ease. Usability has a positive and significant effect on ease of use. Ease has a positive and significant effect on ease of use. Ease has a positive and significant effect on attitudes towards behavior. Ease of use has a positive and significant effect on attitudes towards behavior. Attitudes towards behavior has a positive and significant effect on ease of having a positive effect.